2019
DOI: 10.31289/jab.v5i2.2642
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Pertumbuhan Laba Bank Umum Syariah Di Indonesia

Abstract: AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh variabel determinan atas pertumbuhan laba pada bank umum syariah di Indonesia. Selama periode krisis finansial pada tahun 1997 bank syariah masih dapat menunjukkan kinerja yang relatif lebih baik dibandingkan dengan lembaga perbankan konvensional. dikarenakan lebih rendahnya penyaluran pembiayaan yang bermasalah (non performing loans) pada bank syariah dan tidak terjadinya negative spread dalam kegiatan operasionalnya serta pertumbuhan laba yang dihasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
3
11
0
4
Order By: Relevance
“…(5) in his research proved that the addition of bank office networks has an effect on the growth of Islamic bank assets. However, the results of the study (2) found that the number of offices did not affect the growth of Islamic commercial bank assets.…”
Section: Source: Islamic Banking Statistics 2009-2019mentioning
confidence: 72%
See 4 more Smart Citations
“…(5) in his research proved that the addition of bank office networks has an effect on the growth of Islamic bank assets. However, the results of the study (2) found that the number of offices did not affect the growth of Islamic commercial bank assets.…”
Section: Source: Islamic Banking Statistics 2009-2019mentioning
confidence: 72%
“…Research (9) proves that FDR affects the growth of Islamic bank assets. Research (2) also found that the Financing to Deposit Ratio has an effect on the growth of Islamic commercial bank assets. Similarly, findings (12) prove that FDR has an effect on the growth of Islamic bank assets in Indonesia.…”
Section: The Effect Of Fdr On Asset Growthmentioning
confidence: 97%
See 3 more Smart Citations